Application of laser capture microdissection and proteomics in colon cancer. Issue 4 (1st August 2001) - Lawrie, L C; Curran, S; McLeod, H L; Fothergill, J E; Murray, G I
Abstract : Aims —Laser capture microdissection is a recent development that enables the isolation of specific cell types for subsequent molecular analysis. This study describes a method for obtaining proteome information from laser capture microdissected tissue using colon cancer as a model. Methods —Laser capture microdissection was performed on toluidine blue stained frozen sections of colon cancer. Tumour cells were selectively microdissected. Conditions were established for solubilising proteins from laser microdissected samples and these proteins were separated by two dimensional gel electrophoresis. Individual protein spots were cut from the gel, characterised by mass spectrometry, and identified by database searching. These results were compared with protein expression patterns and mass spectroscopic data obtained from bulk tumour samples run in parallel. Results —Proteins could be recovered from laser capture microdissected tissue in a form suitable for two dimensional gel electrophoresis. The solubilised proteins retained their expected electrophoretic mobility in two dimensional gels as compared with bulk samples, and mass spectrometric analysis was also unaffected. Conclusion —A method for performing two dimensional gel electrophoresis and mass spectrometry using laser capture microdissected tissue has been developed.